Adults with type 1 diabetes who sleep 7–9 hours per night present lower glycemic variability: a cross-sectional study - Duda-Sobczak, Anna; Kulecki, Michal; Pilacinski, Stanislaw; Naskret, Dariusz; Zozulinska-Ziolkiewicz, Dorota (Frontiers in Endocrinology, 2026)
IntroductionThe National Sleep Foundation (NSF) recommends 7–9 hours of sleep per night for adults. Inadequate sleep may negatively impact the outcomes of diabetes treatment.ObjectivesThis study aimed to investigate the associations between sleep duration and quality and glycemic variability in adults with type 1 diabetes.Patients and methods155 participants with type 1 diabetes (73 men, 47%), mean (SD) age 33 (9) years, median (IQR) diabetes duration 12 (8-20) years, completed the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Continuous glucose monitoring (CGM) data were analyzed using Glyculator 3.0. The ANOVA/Kruskal-Wallis test with post-hoc Bonferroni correction analysis, logistic regression, and multivariable linear regression models were used.Results78 participants (50.3%) met the NSF criteria of recommended sleep duration, 56 (36.1%) declared sleeping less than 7h, and 21 (13.6%) sleeping more than 9h. Compared with participants sleeping 7-9h per night, each other group had significantly higher: mean glucose, coefficient of glycemic variability (CV), glycemia risk index (GRI), high blood glucose index (HBGI), mean amplitude of glucose excursions (MAGE), glycemic risk assessment in diabetes equation (GRADE), mean of daily differences (MODD) and lower time-in-range (TIR). No differences in sleep quality, low blood glucose index (LBGI), HbA1c, or diabetes duration were shown among groups. In multivariable logistic regression analysis sleeping 7-9h per night was associated with lower CV, MAGE and MODD after adjustment for age, sex and HbA1c.ConclusionsAdults with type 1 diabetes who sleep 7–9 hours per night present lower glycemic variability compared with those sleeping less or more.